Christian Religious Education and Quality of Life Development An Analysis of The Relationship Between Literacy, Basic Access, and Primary Education Outcomes in Eastern Indonesia - Boiliu, Esti Regina; Wilson Rajagukguk; Thomas Pentury (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study examines the relationship between household literacy, access to basic infrastructure, and the quality of primary education in Eastern Indonesia within the framework of Christian Religious Education values. Using a quantitative explanatory design, the research analyzes national socio-economic data with provinces as the unit of analysis. The model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the predictive power of household access to safe water, access to electricity, and literacy level on primary education outcomes, measured by the average national exam score. The results show that access to safe water (β = 0.294, p < 0.05) and electricity (β = 0.290, p < 0.05) have significant positive effects on education quality, while literacy level (β = 0.081, p > 0.05) is not statistically significant. The model explains 34.7% of the variance in education quality (R² = 0.347). These findings indicate that improving basic infrastructure remains essential to enhancing educational outcomes in Eastern Indonesia. Integrating Christian educational values such as justice, love, and service can further strengthen community motivation and collective responsibility toward equitable education development.